Homeland Crisis and Local Ethnicity: The Toronto Irish and the Cartoons of the Evening Telegram 1910–1914 - Jenkins, William (Urban History Review / Revue d'histoire urbaine, 2010)
This article examines a critique of the “diasporic nationalism” affecting the Irish in Canada through the lens of Toronto, a key destination for Irish immigrants in the nineteenth century. Situated in the period of the third home rule bill and the articulation of opinion about it in Toronto (1910–1914), the article concentrates on the city’s media and particularly the visual content of cartoons published in the strongly pro-empire Evening Telegram. The author demonstrates how a familiar repertoire of Irish symbols and myths was grafted onto the bodies of Toronto’s “Irish” and/or “Ulster” personalities, connecting them with events on the other side of the Atlantic. These satirical representations also informed readings of Irishness in Toronto. They suggest that while a nationalist “green” identity had acquired a respectable and largely middle-class character among Catholics of Irish birth and ancestry in the early twentieth century, there were still forces at work that resisted placement of the latter group on a footing equal to the city’s Protestant majority.